PENINGKATAN PRESTASI BELAJAR MAPEL MATEMATIKA MELALUI PENGGUNAAN ALAT PERAGA SISWA XII TP. 2017/2018 SMKN 1 RAMBAH - Eka Fitri (STKIP ROKANIA, 2019)
This study aims to determine the increase in Mathematics learning achievement material Describe the rules of enumeration, permutation, and combinations through the use of teaching aids students XII TPHP SMK 1 Rambah. The method used is the Class Improvement method. The final result of this study is that with the use of teaching aids that have been implemented, there is an increase in Mathematics learning achievement. Evident from the data on learning outcomes in the first cycle of classical completeness of students reached 58% and the results of classical completeness of students who in the second cycle reached 88%. It can be concluded that the use of the use of teaching aids in improving mathematics learning achievement Material describes the rules for enumeration, permutation, and combinations in students of Class XII TPHP SMK 1 Spread the 2017/2018 Academic Year on target.